Primary Angiosarcoma in the Right Atrium Diagnosed by a Cardiac Tumor Biopsy Using Intracardiac Echocardiography - Naruse, Genki (J Med Ultrasound, 2020)
A 47-year-old woman consulted a doctor due to a persistent cough. Computed tomography revealed a 30 mm × 60 mm intracardiac mass in the right atrium. Because of lung metastasis, her respiratory status did not allow a more invasive procedure, such as general anesthesia. Although intracardiac echocardiography (ICE) during percutaneous transcatheter biopsy (PTB) is not covered by medical insurance, we performed PTB under ICE guidance. Pathology and immunohistochemistry revealed primary cardiac angiosarcoma. Primary cardiac angiosarcoma is a rare tumor with a poor prognosis. After seven cycles of chemotherapy, the pulmonary metastasis was clearly improved. The patient is alive 18 months after the first consult, even though the mortality of angiosarcoma is high. ICE during PTB allowed us to choose appropriate chemotherapy and improve her pulmonary metastasis. ICE during PTB reduces the need for a diagnostic open-chest procedure that requires a more invasive approach.